Collaborative business design : improving and innovating the design of IT-driven business services - Johnson, Brian (IT Governance Publishing, 2017)
Full of useful diagrams and examples (and quotations from an unusual range of sources including Star Trek, Mick Jagger and Oscar Wilde), this book explains how to guide the development, building, program management, and maintenance of IT-driven business services. --